The Matter of Training Alternative Languages from Kindergarten Period - Begmuratov Akmaljon Latifjon o'g'li (Central Asian Journal of Theoretical and Applied Science, 2022)
Today, the process of globalization is beyond the reach of human beings requires learning several other foreign languages. At the moment Studies show that starting this process at an early age gives good results shows